APLIKASI PENENTUAN KARYAWAN TERBAIK DENGAN METODE WP (WEIGHTED PRODUCT) BERBASIS WEB - Fatmawati, Amelia; Marisa, Fitri (JURNAL TEKNOLOGI INFORMASI: Teori, Konsep, dan Implementasi, 2018)
This research is based on the problem that is how the way a company does in motivating itsemployees to keep the spirit in carrying out their work and make a reference in continuing to developcreativity and talent, then made an assessment on employee performance and giving the bestemployee title which will become a parameter in give a bonus if the assessment is good In addition,the award for employees is also intended to encourage selected employees to keep achieving andsimultaneously spur the achievements of other employees. This research aims to create a decisionsupport system in determining the best employees using Weighted Product (WP) which later thisapplication can provide convenience in the selection of the best employees in companies. WP methodis one of the methods used for Multi-Decision Decision Making (MADM). Multiple Attribute DecisionMaking (MADM) is a method used to find the optimal alternative of a number of alternatives withcertain criteria. The essence of MADM is to determine the weight value for each attribute, thenproceed with the ranking process that will select the alternatives already given. The criteria areKnowledge, Skill, Ability, Physical, Attitude. With the weighted value of the decision maker weighs thepreference as: W = (50, 30, 40, 40, 20) for each criterion and then proceed with the previous preweightedweightsofW = (50, 30, 40, 40, 20) Wj W index to j. So for W1 is 50, W2 is 30 and so on.And Î£wj is the sum of W that is 50 + 30 + 40 + 40 + 20 So for the improvement of W1 weight into:(0.27777778), (0.1666667), (0.222222), (0.222222), (0, 111111) and for the value of each specifiedcriterion is a value range of numbers 10 to 100.